2021
DOI: 10.1177/2167479521995462
|View full text |Cite
|
Sign up to set email alerts
|

Side-by-Side Sports Reporters: A Between-Subjects Experiment of the Effect of Gender in Reporting on the NFL

Abstract: Women are more visible than ever in sports media. Yet, extant research has shown that females have endured an array of issues exclusive to their gender. Consistent research updates on gender in sports media is necessary in order to discover whether an increase in numbers has changed the assessment of women in sports media. This study’s objective was to understand how audiences now perceive women in television sports media, specifically as sports reporters covering the NFL. This quantitative experiment employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Moreover, perceived attractiveness positively predicted perceived expertise, which replicates the findings by prior researchers (Brisbane et al, 2021; Davis & Krawczyk, 2010). Together with the above findings, it’s useful to consider the addition of vocal attractiveness on top of physical appearance in future sportscaster credibility studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, perceived attractiveness positively predicted perceived expertise, which replicates the findings by prior researchers (Brisbane et al, 2021; Davis & Krawczyk, 2010). Together with the above findings, it’s useful to consider the addition of vocal attractiveness on top of physical appearance in future sportscaster credibility studies.…”
Section: Discussionsupporting
confidence: 88%
“…Within sport, Davis and Krawczyk (2010) found that perceived physical attractiveness of female sportscasters is positively associated with audience perceptions of their expertness and competence. Similarly, Brisbane et al (2021) suggested that perceived attractiveness of a female sportscaster is positively related to her perceived knowledge. As society places an emphasis on women’s physical attractiveness, and female sportscasters are believed to be hired largely because of their looks (Sheffer & Schultz, 2007), audiences are more likely to consider physical attractiveness as an important dimension of expertise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though radio and television broadcasting now have a greater percentage of women working in sports than they used to have (cf. Boyle, 2006;Brisbane, 2021), studies have demonstrated the disadvantages that women are confronted with, especially when it comes to credibility, stereotyping, and sexism (Etling and Young, 2007;Mastro et al, 2012;Mudrick et al, 2017). In TV sports broadcasting, female reporters are mostly relegated to reporting from the side-lines, while their male colleagues do more prominent work, such as providing commentary and game analysis (Messner et al, 2000).…”
Section: Gender In Sports Journalismmentioning
confidence: 99%
“…They consider female sports reporters and presenters less trustworthy and knowledgeable than male reporters (Mitrook and Dorr, 2001;Toro, 2005;Etling and Young, 2007). However, a major breakthrough was reported in a research by Gayle Jansen Brisbane et al (2021). Brisbane's study which focused on the work of journalists within National Football League in the USA was the first ever to assert significantly better acceptance by audiences of women sports broadcasters and a diminishing tendency to stereotype women.…”
Section: Gender In Sports Journalismmentioning
confidence: 99%
See 1 more Smart Citation